Gamifying Teacher Education with FantasyClass: Effects on Attitudes towards Physics and Chemistry among Preservice Primary Teachers - Gregorio Jiménez-Valverde; Carlos Heras-Paniagua; Noëlle Fabre-Mitjans; Genina Calafell-Subirà (MDPI AG, 2024)
This study investigates the impact of structural gamification, using the digital platform FantasyClass, on the attitudes and motivation of preservice primary education teachers towards physics and chemistry. Employing a mixed-methods approach, the research combined quantitative and qualitative data collection and analysis involving 65 second-year university students over a 14-week course. The quantitative component was framed within a quasi-experimental pre-post design, allowing for the comparison of students' attitudes and motivations before and after the gamified intervention. The qualitative component was designed to complement the quantitative findings. Quantitative analysis revealed significant improvements in students' perceptions and motivation, with notable increases in positive attitudes towards these sciences. Qualitative data further highlighted enhanced interest and enjoyment, with students reporting greater engagement and a shift in their perception of physics and chemistry as accessible and enjoyable. The study also noted an increase in self-confidence among future teachers and improved teaching self-efficacy. The findings suggest that integrating gamification in initial primary science teacher education can effectively foster more favorable attitudes, enhance motivation towards science, and improve teaching confidence. Future research should explore long-term impacts, as well as personalized gamification approaches to cater to different types of learners and maximize educational effectiveness.